2009
DOI: 10.1186/1471-2148-9-99
|View full text |Cite
|
Sign up to set email alerts
|

Impact of duplicate gene copies on phylogenetic analysis and divergence time estimates in butterflies

Abstract: Background: The increase in availability of genomic sequences for a wide range of organisms has revealed gene duplication to be a relatively common event. Encounters with duplicate gene copies have consequently become almost inevitable in the context of collecting gene sequences for inferring species trees. Here we examine the effect of incorporating duplicate gene copies evolving at different rates on tree reconstruction and time estimation of recent and deep divergences in butterflies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 79 publications
(96 reference statements)
5
28
2
Order By: Relevance
“…The phylogeny estimated under a relaxed clock model in BEAST shows diversification dynamics that differ from previous estimates, with the deeper splits between the genera of Heliconiini estimated as substantially older than previously inferred with mitochondrial data, but younger than estimated with a small sample of nuclear genes (Table 1) Pohl et al 2009). The most species-rich genera Heliconius and Eueides separated 18.5 (95% highest posterior density: 16.5-20.4) Ma and both started to diversify, respectively, 11.8 (10.5-13.4) Ma and 10.2 (8.9-11.7) Ma.…”
Section: Tempo Of Diversificationcontrasting
confidence: 69%
See 2 more Smart Citations
“…The phylogeny estimated under a relaxed clock model in BEAST shows diversification dynamics that differ from previous estimates, with the deeper splits between the genera of Heliconiini estimated as substantially older than previously inferred with mitochondrial data, but younger than estimated with a small sample of nuclear genes (Table 1) Pohl et al 2009). The most species-rich genera Heliconius and Eueides separated 18.5 (95% highest posterior density: 16.5-20.4) Ma and both started to diversify, respectively, 11.8 (10.5-13.4) Ma and 10.2 (8.9-11.7) Ma.…”
Section: Tempo Of Diversificationcontrasting
confidence: 69%
“…Although most age estimates for Heliconius agree with other studies, the deeper nodes are older than previously suggested (Table 1). There is little agreement on the dates above the species level, and the studies to date either suffer from insufficient taxon sampling (Pohl et al 2009;Wahlberg et al 2009;Cuthill and Charleston 2012; Table 3), or use markers unlikely to be informative above a relatively low level of divergence ). For instance, the mean age of the split between Heliconius and Agraulis is estimated as 32 Ma in the study of Pohl et al (2009), which includes only three species of Heliconiini; 26.5 Ma in Wahlberg et al (2009), including one species per genus; or 23.8 Ma in the present study ( Fig.…”
Section: Divergence Time Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic relationships between species are derived from a recent molecular phylogeny (47) after retaining nodes with bootstrap support ≥0.98. Estimated age of Heliconius radiation is derived from a recent molecular clock study (48). Only a subset of Heliconius wing pattern diversity is represented here.…”
Section: Discussionmentioning
confidence: 99%
“…This process has occurred frequently, and sometimes rapidly, in evolutionary time (Pohl et al, 2009;Gojobori and Innan, 2009;Trezise and Collin, 2005). The recent expansion in genomic data of invertebrates has shown that even animals lacking morphologically complex eyes are often rich in opsin genes.…”
Section: A M Sweeney and Othersmentioning
confidence: 99%